Cochlear Implant Surgical Technique: Our Experience - Kirtane, Milind Vasant; Chavan, Kashmira Prakash (Annals of Otology and Neurotology, 2018)
Introduction Different surgical approaches have been adopted for cochlear implantation, with cortical mastoidectomy–posterior tympanotomy being the most commonly followed technique.Method In this article, we describe the surgical technique for cochlear implant followed at our center, which has been successfully implemented in more than 2,500 cochlear implant surgeries. Cochlear implant surgery using the cortical mastoidectomy–posterior tympanotomy technique has been performed in more than 2,500 cases with some modifications to the original technique over a period of time.Results In spite of not using tie-down holes and securing down the receiver–stimulator with sutures, no cases of receiver–stimulator displacement or outward electrode migration have been noted with the current technique of creating a snug-fitting subperiosteal pocket along with a hook for the electrode array.Conclusion Adhering to a strict intraoperative surgical protocol plays an extremely important role in carrying out successful cochlear implant surgeries with minimal complications.
Keywords: cochlear implants; surgical technique; posterosuperior musculoperiosteal flap